Evaluation of the influence of the impression technique, scanning direction and type of scanner on the accuracy of the final model - Viegas, Diogo Cabecinha; Mourão, João Tiago; Roque, Joao Carlos; Riquieri, Hilton; Fernandes, João; Arrobas, Fernando Vasconcelos; Diamantino, Pedro Jacy Santos; Saavedra, Guilherme S. F. Anzaloni (Brazilian Dental Science, 2020)
Objective: The purpose of this study is to evaluate the influence of the type of scanner and scanning direction on the accuracy of the final cast. Material and Methods: A partial master cast was used as a reference. A total of 128 scans were obtained and divided into two groups: the conventional method and the digital method. The digital group was divided into three groups: TRIOS 3, Omnicam and CS 3600. Each of these groups was subdivided according to the scanning direction, and each scan was overlaid on the digital reference cast to measure the trueness and precision of the procedures. Results: The overall precision values for the type of impression were 59.89 ± 13.08 mm for conventional and 13.42 ± 4.28 mm for digital; the values for trueness were 49.37 ± 19.13 mm for conventional and 53.53 ± 4.97 mm for digital; the scanning direction trueness values were 53.05 ± 4.36 mm for continuous and 54.03 ± 5.52 mm for segmented; and the precision values were 14.18 ± 4.67 mm for continuous and 12.67 ± 3.75 mm for segmented (p> 0.05). For the scanner type, the trueness values were 50.06 ± 2.65 mm for Trios 3, 57.45 ± 4.63 mm for Omnicam, and 52.57 ± 4.65 mm for Carestream; and those for precision were 11.7 ± 2.07 mm for Trios 3, 10.09 ± 2.24 mm for Omnicam, and 18.49 ± 2.42 mm for Carestream (p <0.05). Conclusions: The digital impression method is the most favorable method regarding precision; in terms of trueness, there are no differences between the types of impressions. KEYWORDS Conventional impression; Intra oral impression; Accuracy; Trueness.